Analysis of claim ratio, risk-based capital and value-added intellectual capital: a comparison between family and general takaful operators in Malaysia / Nur Amalina Syafiqa Kamaruddin ... [et al.] - Kamaruddin, Nur Amalina Syafiqa; Ishak, Norizarina; Hamzah, Siti Raihana; Abdul Halim, Nurfadhlina; Nurullah Rasade, Ahmad Fadhly (2021)
Insurance industry played important roles in world especially in well-developed countries. Takaful which has been getting on-going popularity in insurance sector must maintain good market growth. Thus, this study aimed to assess the financial performance of Takaful operators through Claim Ratio, Risk-Based Capital (RBC) and Intellectual Capital. The study was conducted using panel data set of 15 listed Takaful operators in Malaysia over the period 2015-2019, taken from the operators’ audited financial statements. The results were obtained by computing Claim Ratio, minimum capital level required in RBC and the Value-Added Intellectual Capital (VAIC) score. The result of Claim Ratio showed that family takaful fund has higher Claim Ratio which indicated low profit as compared to general takaful fund. The RBC result also supported that the general takaful performed better than most of family takaful by fulfilled the supervisory target capital level of 130% as required by Bank Negara Malaysia (BNM). As for VAIC score, most of the Takaful operators showed positive VAIC scores which mean they able to fully utilized company’s resources that lead to an out-standing management leader stewardship. This study further assists Takaful operators to incorporate the Intellectual Capital method for better improvement in assessing their future performance.